2021
DOI: 10.3390/cells10051002
|View full text |Cite
|
Sign up to set email alerts
|

KLF5 Is Activated by Gene Amplification in Gastric Cancer and Is Essential for Gastric Cell Proliferation

Abstract: Gastric cancer is the third leading cause of cancer death worldwide. In this study, we tried to clarify the function of KLF5 in gastric cancer. Copy number variation (CNV) and the expression of KLF5 were interrogated in public datasets. The clinical significance of KLF5 amplification and gene expression in gastric cancer were evaluated. The function of KLF5 in cell proliferation was studied in gastric cancer cell lines and organoids. We found that KLF5 amplification mainly occurred in the chromosome instable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous research has shown that members of the KLF family are overexpressed in tumor tissues or cell lines. KLF5 overexpression has been discovered in gastric cancer, and it has been linked to greater tumor sizes and later tumor (T) stages [ 18 ]. KLF8 was shown to be overexpressed in human HCC cell lines and samples from individuals with the disease [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that members of the KLF family are overexpressed in tumor tissues or cell lines. KLF5 overexpression has been discovered in gastric cancer, and it has been linked to greater tumor sizes and later tumor (T) stages [ 18 ]. KLF8 was shown to be overexpressed in human HCC cell lines and samples from individuals with the disease [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, GATA6 has been shown to cooperate with other TFs, such as KLF5, to promote cancer development [ 34 , 35 ]. In CRC, GATA6 and Krüppel-like factor 5 (KLF5) have been implicated in the regulation of cancer stem cell characteristics and chemoresistance [ 36 , 37 ]. Signal transducer and activator of transcription 3 (STAT3) is a TF involved in various cellular processes, including cell growth, differentiation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Chinese institutions formed closer collaborations within the country than with external agencies. Chinese researchers are characterized by a lack of influence, which may be attributed to the lack of external collaboration(s), thus necessitating encouragement to form partnerships with institutions around the world[ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%